Adaptations cinématographiques de pièces de théâtre à Lyon (1929-1939) : promotion mutuelle entre le théâtre des Célestins et les salles de cinéma - Marylin Marignan (Mise au Point)
This article suggests revising the notion of adaptation, in the thirties, in Lyon, by focusing not only on “competition” between the theater and the cinema but also on “exchange”, “complementarity” and “mutual promotion”. During this period, the press spreads widely the idea that the cinema, by turning more to the plays, the playwrights and the actors of the dramatic art, had caused harm to itself and theater. However, the movies adaptations of plays are going to make an important advertising for the théâtre des Célestins which registers again some these old plays with sometimes the actors of this movies. At the same time, the movies adaptations of plays are going to know an immense success with the public of Lyon in spite of bad criticisms.